Application of the 4th Order Runge Kutta Method in Smoking Dynamics Modelling - Dayang Manis; Maya Sari Syahrul (Journal of Applied Mathematics and Modelling, 2025)
The dynamics of smoking is a problem that has captured the world's attention both in health and social life issues. In modeling, the rate of change in smoking dynamics, there are four populations that affect each other, namely potential smokers (P), light smokers (S), heavy smokers (T) and smokers who have quit smoking (Q). Two equilibrium points were obtained, namely  which describes the smoking point, and  which describes the non-smoking point. The results of numerical simulations on the model show that the absence of interaction between the potential population of smokers (P) and the population of light smokers (S) results in a decrease in the rate of change in the population of light smokers (S). Meanwhile, the interaction between the potential smoker population (P) and the light smoker population (S) resulted in an increase in the rate of change in the light smoker population (S). So, to limit the growth of the number of light smokers, it is necessary to limit the interaction between the potential population of smokers (P) and the population of light smokers (S).